1996
DOI: 10.1007/s0021663540763
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamic surface model for caesium sorption on bentonite

Abstract: Caesium sorption on Wyoming bentonite MX-80 has been studied in solutions of NaCl, KCl, MgCl(2), CaCl(2), NaNO(3) and Ca (NO(3))(2) of concentrations varying between 0.025 and 1 mol/L, as well as in a weakly saline (I=0.004 ml/L) and a strongly saline (I=0.46 mol/L) natural groundwater. These experiments have been used to derive a thermodynamic model for the interaction of caesium with the bentonite surface in accordance with a surface chemical model, including acid/base reactions developed recently for montmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…D e trends for cations and anions could not be explained by the conventional pore diffusion model alone, considered in terms of porosity (e), tortuosity (s) and (geometric) constrictivity (d g ) factor, and the tracer diffusivity in bulk liquid water, D w (m 2 s À1 ), from Van Brakel and Heertjes (1974): Bradbury and Baeyens (2000). b Wanner et al (1996). c Tachi et al (2009b).…”
Section: Underlying Assumptions For Diffusion Modelingmentioning
confidence: 95%
See 3 more Smart Citations
“…D e trends for cations and anions could not be explained by the conventional pore diffusion model alone, considered in terms of porosity (e), tortuosity (s) and (geometric) constrictivity (d g ) factor, and the tracer diffusivity in bulk liquid water, D w (m 2 s À1 ), from Van Brakel and Heertjes (1974): Bradbury and Baeyens (2000). b Wanner et al (1996). c Tachi et al (2009b).…”
Section: Underlying Assumptions For Diffusion Modelingmentioning
confidence: 95%
“…Maes et al (2008) and Van Loon et al (2009) also tested this three-site model to describe Cs + isotherms on Boom clay and Opalinus clay, respectively. For smectite, the one-site ion exchange model developed by Wanner et al (1996) was used. This one-site model can describe Cs + sorption in various types of smectite and bentonite, and solution conditions (Wanner et al, 1996;Ochs et al, 2001;Tachi et al, 2009a), although it has been confirmed that Cs + sorbs on smectite as inner-sphere and outer-sphere complexes by NMR (Kim et al, 1996b) and EXAFS (Bostick et al, 2002).…”
Section: Modeling Of Cs Sorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…uranium, plutonium, neptunium, americium, cesium, thorium, technetium and selenium (see, for example, references Baston et al 1995;Missana et al 2004;Hurel et al 2009;Nagasaki et al 1999;Shibutani et al 1994;Tsai et al 2001;Wang et al 2005;Wanner et al 1996;Xu et al 2006). In particular, the sorption of strontium onto bentonite has been the object of different studies in Na-and Ca-bentonite (Choi and Oscarson 1996;Eriksen et al 1999;Khan et al 1995;Galamboš et al 2009;Muurinen et al 1987;Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%